2001
DOI: 10.1007/s004640080173
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastases are less established after gasless laparoscopy than after carbon dioxide pneumoperitoneum and laparotomy in a mouse model

Abstract: These results suggest that the defense against liver metastasis is better preserved after the gasless procedure than after laparotomy and carbon dioxide pneumoperitoneum in the reported animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…At the end of insufflation, the catheter was removed. In the rats receiving the gasless procedure, two fixable retraction wires connected with a metallic plate lying over the abdomen longitudinally inserted under the abdominal skin, and the abdomen was elevated mechanically by suspending the metallic plate for 30 min [5]. Seven days after the procedures, 10 ml of PBS was injected intraperitoneally, and the rat abdomen was agitated gently to mix the fluid in the cavity for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of insufflation, the catheter was removed. In the rats receiving the gasless procedure, two fixable retraction wires connected with a metallic plate lying over the abdomen longitudinally inserted under the abdominal skin, and the abdomen was elevated mechanically by suspending the metallic plate for 30 min [5]. Seven days after the procedures, 10 ml of PBS was injected intraperitoneally, and the rat abdomen was agitated gently to mix the fluid in the cavity for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…One alternative to CO 2 pneumoperitoneum is mechanical elevation of the abdominal wall (gasless procedure). However, only a few experiments have been performed to compare the gasless procedure and CO 2 pneumoperitoneum in terms of oncologic benefit [2,5]. Therefore, this study was performed to determine which of the methods is optimal for minimal access tumor surgery instead of blindly using CO 2 pneumoperitoneum.…”
mentioning
confidence: 97%
“…Previous applications of the CC531s model in experimental laparoscopy were performed by intrasplenic 7 or intraportal 8,9 injection of the tumour cells, leading to multiple hepatic metastases after haematogeneous spread. In contrast, CC531s cells were injected subcapsularly in a nonsurgical oncological study to induce well-localised and accessible liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of experimental studies have assessed the influence of laparoscopy on postoperative outcome of colorectal carcinoma using various models. The assessment of haematogeneous hepatic tumour spread in rats 7,8 and mice 9 and of renal or cutaneous tumour growth after subcapsular 10 or subcutaneous 11 injection of colorectal carcinoma cells have led to controversial for and against arguments for the laparoscopic technique. Importantly, hepatic macrophages have been described as playing a key oncological role in cellular antitumoural defence in respect of enhanced experimental tumour growth following selective depletion of phagocytotic cells.…”
mentioning
confidence: 99%
“…However, we demonstrated that CO 2 pneumoperitoneum enhanced liver metastasis in comparison with the control group, and also that this effect might be associated with the induction of ICAM-1 and TNF-a in establishing liver metastasis. For the inhibition of liver metastasis after CO 2 pneumoperitoneum, it may be necessary to prevent portal blood flow depression by means of a gasless procedure or lower insufflation pressure [9,10].…”
Section: B-actinmentioning
confidence: 99%